Information Needs of Cassava Farmer-Processors on Cassava Value Addition Technologies in Oyo State, Nigeria - Rasak Bamidele Olajide; Lateef O. Sanni; Godwin Atser; Alfred Dixon; Ibukunoluwa O. Oladokun (Journal of Agricultural Extension, 2021)
The rapidly expanding end-use markets for cassava implies a surge in the production and processing of cassava roots into various value-added forms. This study investigated the information needs of cassava farmers on cassava value addition technologies in Oyo State, Nigeria, to ascertain areas of information gap for farmers to maximally exploit the opportunities inherent in the product value addition. Using a multistage sampling procedure, 130 registered cassava farmers were sampled and interviewed. Data were collected on respondents’ personal and enterprise characteristics, access to information, perceived benefits and constraints to accessing information and information needs on cassava value addition. Data were analysed using percentages, means and correlational analysis at p=0.05. Results indicate that respondents were married (91.5%), with mean farm size and farming experience of 2.3 ha and 20.1±13.8 years, respectively, while fellow farmers ranked first as major source of information. Though respondents were constrained with low income (70.0%), they reckoned that if they had access to information on value addition, their postharvest loss will be reduced (89.2%). Respondents had information gap on information needs on cassava adhesives (1st), glucose syrups (2nd) and confectionaries (3rd). Farming experience (r = -.236), constraints (r = -.288) and access to sources of information were significantly related to respondents’ information needs. It is recommended that information on improved cassava value addition technologies be made available to cassava farmers through relevant sources, especially during emergencies coupled with hands –on training for effective application of information acquired.